NEEDS IDENTIFICATION FOR TRANSFORMATIONAL LEADERSHIP OF SECONDARY COLLEGE DEANS IN VOCATIONAL COLLEGES—A CASE STUDY OF HONGHE VOCATIONAL AND TECHNICAL COLLEGE - Zhang, Yu; Chanboon, Somyos; Mungthaisong, Sornchai (Chinese Journal of Social Science and Management, 2026)
Purpose: Amid the transformation of higher vocational education and the “Double-High Plan”, this study used Honghe Vocational and Technical College as a case, integrating the localized four dimensions of transformational leadership with the Five-Forces Leadership Model, and developing a nine-dimensional analytical framework to identify key leadership needs of secondary college deans and propose targeted improvement suggestions. Study Design/Methodology/Approach: A mixed-methods approach was used. A measurement instrument was developed based on TLQ’s four dimensions and the Five Forces model. Using stratified purposive sampling, 419 valid questionnaires were collected. SPSS was used to conduct reliability and validity tests, descriptive statistics, correlation analysis, and multiple regression analysis. Additionally, semi-structured interviews were conducted with 20 participants, including senior leaders, middle-level administrators, teachers, and enterprise representatives; thematic analysis was used to further interpret and supplement the quantitative findings. Findings: The overall level of deans’ transformational leadership was moderate (M = 4.03). “Moral Modeling” scored the highest (M = 4.14), while “Influence” scored the lowest (M = 3.94). Regression results implied that “Leadership Charisma, Decisiveness, Individualized Consideration, Moral Modeling, and Influence” significantly and positively predicted leadership effectiveness (β = 0.202-0.281, p < 0.001). Interview data further revealed weaknesses in policy implementation, communication and feedback, external resource linkages, and teacher support. Originality/Value: This study developed and validated an integrated nine-dimensional measurement framework, offering a quantifiable diagnostic tool, an evidence base for improving middle-level governance in border-region vocational colleges, and supporting leadership development and policy implementation.